Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.14802/jmd.17038
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Conversion between the Mini-Mental State Examination and Montreal Cognitive assessment in Korean Patients with Parkinson’s Disease

Abstract: Objective Two conversion tables between the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) have recently been established for Parkinson’s disease (PD). This study aimed to validate them in Korean patients with PD and to evaluate whether they could be influenced by educational level.Methods A total of 391 patients with PD who undertook both the Korean MMSE and the Korean MoCA during the same session were retrospectively assessed. The mean, median, and root mean squared error (RMSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…In accord with previous classical test theory-based conversions (Bergeron et al, 2017;Kim et al, 2018;Lawton et al, 2016;Roalf et al, 2013;van Steenoven et al, 2014;Trzepacz et al, 2015) (Perneczky et al, 2006;Rambeau et al, 2019).…”
Section: Conversion From Mmse To Mocasupporting
confidence: 87%
See 1 more Smart Citation
“…In accord with previous classical test theory-based conversions (Bergeron et al, 2017;Kim et al, 2018;Lawton et al, 2016;Roalf et al, 2013;van Steenoven et al, 2014;Trzepacz et al, 2015) (Perneczky et al, 2006;Rambeau et al, 2019).…”
Section: Conversion From Mmse To Mocasupporting
confidence: 87%
“…cognitive impairment, elderly, Rasch analysis, selective surgery, the Mini-Mental State Examination, the Montreal Cognitive Assessment Linking and equating techniques provide approaches to make different scales comparable (von Davier, 2013). Based on classical test theory, previous studies have established conversion tables between MMSE and MoCA using an equipercentile equating method with or without log-linear smoothing, in samples of patients with MCI, dementia (Bergeron et al, 2017;Roalf et al, 2013Roalf et al, , 2017Saczynski et al, 2015;Trzepacz et al, 2015), Parkinson's disease (Kim et al, 2018;Lawton et al, 2016;van Steenoven et al, 2014), or stroke (Wong et al, 2018) (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“… MMSE, Mini-Mental State Examination (min = 0, max = 30, score ≥ 24 normal, score 18-23 MCI) ( 44 ); IADL, Instrumental Activities of Daily Living Scale ( 45 ); BBT, Box and Blocks Test ( 34 ) performed with right and left hand, respectively; JTHFT, Jebsen-Taylor Hand Function Test ( 24 ) total score across six tasks; Pinch Gauge instructions for tip, key and palmer pinch strength, average reported ( 35 ); NHPT, Nine-Hole Peg Test ( 22 ) finger dexterity test . * Group difference tested using Mann-Whitney U-test.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that MMSE and MoCA can be useful for screening cognitive impairment in less educated patients 18. In study on Koreans by Kim et al,16 approximately 30% of patients had 6 or fewer years of education. Although conversion scales have satisfactory validity in highly educated and less educated patients, it is also necessary to confirm validity in patients with low levels of education.…”
Section: Discussionmentioning
confidence: 99%
“…Two MoCA-MMSE conversion scales developed by van Steenoven et al15 and Lawton et al14 have reasonable validity. Recently, it has been shown that both of these MoCA-MMSE conversion scales are useful for transforming MoCA scores into converted MMSE scores in Korean patients with PD 16. However, patients with other subtypes of dementia were not assessed.…”
Section: Introductionmentioning
confidence: 99%